2020
DOI: 10.1097/sla.0000000000004218
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Screening for COVID-19 in Asymptomatic Patients Before Elective or Emergency Surgery Using Chest CT and RT-PCR (SCOUT)

Abstract: Objective: To determine the yield of preoperative screening for COVID-19 with chest CT and RT-PCR in patients without COVID-19 symptoms. Summary of Background Data: Many centers are currently screening surgical patients for COVID-19 using either chest CT, RT-PCR or both, due to the risk for worsened surgical outcomes and nosocomial spread. The optimal design and yield of such a strategy are currently unknown. Methods: This multicenter study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 27 publications
5
42
1
2
Order By: Relevance
“…This study showed no additional benefit to performing CT in addition to a single swab test, meaning that the additional cost and organizational burden of CT as a screening test in asymptomatic patients is unlikely to be justified. This corroborates the findings of a multicentre study of 2093 patients undergoing surgery in the Netherlands, in which the incremental yield of thoracic CT in asymptomatic patients was slight, at 0.4 per cent 9 . Similarly, in a small series 22 , high-resolution CT chest added very little additional value and a high resource cost, with just 3 of 386 patients with a negative swab who had thoracic CT having surgery postponed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study showed no additional benefit to performing CT in addition to a single swab test, meaning that the additional cost and organizational burden of CT as a screening test in asymptomatic patients is unlikely to be justified. This corroborates the findings of a multicentre study of 2093 patients undergoing surgery in the Netherlands, in which the incremental yield of thoracic CT in asymptomatic patients was slight, at 0.4 per cent 9 . Similarly, in a small series 22 , high-resolution CT chest added very little additional value and a high resource cost, with just 3 of 386 patients with a negative swab who had thoracic CT having surgery postponed.…”
Section: Discussionsupporting
confidence: 89%
“…On the other, there is a time and cost burden of testing, with uncertainty around the best strategy and variable global availability 4–6 . The mainstay of testing is nasopharyngeal swab test with quantitative reverse transcriptase–PCR (RT–qPCR) to detect SARS-CoV-2 viral RNA 7 , 8 , although preoperative CT has also been suggested, especially before major surgery 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have reported chest CT of asymptomatic SARS-CoV-2 infections. However, most of these asymptomatic studies were cross-sectional and focused on summarizing of CT features or screening 25 , 37 - 39 . A comprehensive and longitudinal study (including screening, CT features and evolution of asymptomatic SARS-CoV-2 infections) was scarcely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses, anaesthetists and surgeons were certainly infected in the course of their work during Victoria's second wave, despite none being in the preoperative testing cohort reported by the eight Victorian hospitals 6 . There were also 596 non‐clinical staff infected, 343 (58%) of them were acquired in the workplace 8 . The third risk is to other patients who may contract coronavirus disease in hospital by coming into contact with infected patients.…”
mentioning
confidence: 99%
“…Other countries, far worse afflicted by their waves of coronavirus disease than Victoria, have reported rates of preoperative testing exceeding 1%. 8 There are three reasons to identify which patients being admitted to hospital for elective surgery have coronavirus disease. The first is to minimize their risk of morbidity and mortality in the postoperative period.…”
mentioning
confidence: 99%